2020
DOI: 10.3390/ijerph17082694
|View full text |Cite
|
Sign up to set email alerts
|

Built Environment and Childhood Weight Status: A Multi-Level Study Using Population-Based Data in the City of Hannover, Germany

Abstract: In recent years, built environmental characteristics have been linked to childhood overweight, but the results remain inconsistent across studies. The present study examines associations between several built environmental features and body weight status (BMI) z-score among a large sample of preschool children in the city of Hannover, Germany. Walkability (Index), green space availability, and playground availability related to preschool children’s home environments were measured using data from OpenStreetMap … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 59 publications
0
11
0
1
Order By: Relevance
“…Community planning provides the policy foundation for zoning codes and services which meet children’s needs [ 20 , 21 ]. Most studies focus on the relation between the physical built environment and child health, such as streets and sidewalks to ensure walkability [ 8 , 22 , 23 ], neighborhood characteristics such as mixed use and access to play spaces [ 9 , 24 , 25 , 26 , 27 , 28 ], and housing characteristics [ 13 , 29 ].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Community planning provides the policy foundation for zoning codes and services which meet children’s needs [ 20 , 21 ]. Most studies focus on the relation between the physical built environment and child health, such as streets and sidewalks to ensure walkability [ 8 , 22 , 23 ], neighborhood characteristics such as mixed use and access to play spaces [ 9 , 24 , 25 , 26 , 27 , 28 ], and housing characteristics [ 13 , 29 ].…”
Section: Literature Reviewmentioning
confidence: 99%
“…For example, although the walkability score (e.g., intersection density and land use mix) was calculated and identified as positively correlated with PA among children in Spain, 25,27 Australia, 26 the United States 31,32 and New Zealand, 29 this correlation was not found in two other studies conducted in Scotland 30 and Germany 33 . Furthermore, the correlation between walkability scores and obesity is far from conclusive: Although the negative correlation between walkability scores and the childhood obesity index (e.g., BMI) was found to be significant in the United States 34,35 and Malaysia, 36 this correlation was not significant in Germany 37 . In addition, one study showed that the walkability score was positively associated with the risk of overweight or obesity in England 38 …”
Section: Introductionmentioning
confidence: 94%
“…Nevertheless, there is a lack of quantitative regulations on the service level of children's activity venues. This lack of children's activity venues will have a negative impact on children's PA levels and potentially result in serious health problems for children [51][52][53]. Increasing the supply of children's activity venues in parks and improving the accessibility of children's activity venues could be an effective way to improve the deteriorating trend of children's health [54,55].…”
Section: Quantitative Evaluation Can Provide a Basis For The Optimiza...mentioning
confidence: 99%